Evaluation of Kidney Stones with Reduced–Radiation Dose CT: Progress from 2011−2012 to 2015−2016—Not There Yet - Weisenthal, Karrin; Karthik, Priyadarshini; Shaw, Melissa; Sengupta, Debapriya; Bhargavan-Chatfield, Mythreyi; Burleson, Judy; Mustafa, Adel; Kalra, Mannudeep; Moore, Christopher (Radiology, 2018)
Purpose To determine if the use of reduced-dose computed tomography (CT) for evaluation of kidney stones increased in 2015-2016 compared with that in 2011-2012, to determine variability in radiation exposure according to facility for this indication, and to establish a current average radiation dose for CT evaluation for kidney stones by querying a national dose registry. Materials and Methods This cross-sectional study was exempt from institutional review board approval. Data were obtained from the American College of Radiology dose registry for CT examinations submitted from July 2015 to June 2016. Study descriptors consistent with single-phase unenhanced CT for evaluation of kidney stones and associated RadLex® Playbook identifiers (RPIDs) were retrospectively identified. Facilities actively submitting data on kidney stone-specific CT examinations were included. Dose metrics including volumetric CT dose index, dose-length product, and size-specific dose estimate, when available, were reported, and a random effects model was run to account for clustering of CT examinations at facilities. A z-ratio was calculated to test for a significant difference between the proportion of reduced-radiation dose CT examinations (defined as those with a dose-length product of 200 mGy · cm or less) performed in 2015-2016 and the proportion performed in 2011-2012. Results Three hundred four study descriptors for kidney stone CT corresponding to data from 328 facilities that submitted 105 334 kidney stone CT examinations were identified. Reduced-dose CT examinations accounted for 8040 of 105 334 (7.6%) CT examinations, a 5.6% increase from the 1010 of 49 903 (2%) examinations in 2011-2012 (P < .001). Mean overall dose-length product was 689 mGy · cm (95% confidence interval: 667, 712), decreased from the mean of 746 mGy · cm observed in 2011-2012. Median facility dose-length product varied up to sevenfold, from less than 200 mGy · cm to greater than 1600 mGy · cm. Conclusion Use of reduced-radiation dose CT for evaluation of kidney stones has increased since 2011-2012, but remains low; variability of radiation dose according to facility continues to be wide. National mean CT radiation exposure for evaluation of renal colic during 2015-2016 decreased relative to 2011-2012 values, but remained well above what is reasonably achievable. RSNA, 2017.